Implementasi Sistem Informasi Geografis dalam Memvisualisasikan Tingkat Kualitas Udara di Jakarta secara Real Time Berbasis Web - Theodorus Ansell; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Knowing the Air Quality index is important. Humans sometimes forget about this and keep doing their activities without realizing it has polluted the air. Pollution activities can endanger human health and can cause death. Therefore, in this study, researchers want to implement a geographic information system to visualize air quality data in Jakarta in real time. The purpose of this study is to display the air quality in Jakarta in real time to the people in Jakarta in the hope of creating a sense of concern for the level of air quality. This research uses research and development research and prototype system development methods. The result of this research is a GIS website that displays the value of air quality in Jakarta in real time and information about the development of air quality in Jakarta so far.